1996
DOI: 10.1007/s004010050566
|View full text |Cite
|
Sign up to set email alerts
|

Myopathology in patients with a Noonan phenotype

Abstract: Two patients with a Noonan phenotype and progressive hypertrophic obstructive cardiomyopathy are described, in whom abnormal histopathological changes in striated musculature were detected. In both patients an increased density of muscle spindles was found at biopsy. The significance of an increased density of muscle spindles in patients with Noonan phenotype can only be speculated. The question is raised of whether these changes are a distinct feature within the spectrum of patients with Noonan phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…To date, a myopathy with excess of neuromuscular spindles has been described in only five cases; four of these harbored heterozygous mutations in the HRAS gene [3]. One of the previously reported patients presented with Noonan syndrome-like facial anomalies and hypertrophic obstructive cardiomyopathy [6].…”
Section: Discussionmentioning
confidence: 97%
“…To date, a myopathy with excess of neuromuscular spindles has been described in only five cases; four of these harbored heterozygous mutations in the HRAS gene [3]. One of the previously reported patients presented with Noonan syndrome-like facial anomalies and hypertrophic obstructive cardiomyopathy [6].…”
Section: Discussionmentioning
confidence: 97%
“…Our study population consisted of four previously reported patients [5][6][7] and one newly ascertained case. All patients presented with congenital muscular weakness.…”
Section: Methodsmentioning
confidence: 99%
“…This biopsy demonstrated abnormal morphology on light microscopy with an excess of muscle spindles. These changes were interpreted as rare myopathic changes that could be added to the list of occasional findings associated with NS [de Boode et al, 1996]. The patient had feeding problems and failure to thrive.…”
Section: Casementioning
confidence: 97%